Clinician engagement in the ADAPTABLE (Aspirin Dosing: A Patient-centric Trial Assessing Benefits and Long-Term Effectiveness) trial. (August 2021) - Kochar, Ajar; Summers, Mary B; Benziger, Catherine P; Marquis-Gravel, Guillaume; DeWalt, Darren A; Pepine, Carl J; Gupta, Kamal; Bradley, Steven M; Dodson, John A; Lampert, Brent C; Robertson, Holly; Polonsky, Tamar S; et al.
Background: ADAPTABLE (Aspirin Dosing: A Patient-centric Trial Assessing Benefits and Long-Term Effectiveness) is a pragmatic clinical trial examining high-dose versus low-dose aspirin among patients with cardiovascular disease. ADAPTABLE is leveraging novel approaches for clinical trial conduct to expedite study completion and reduce costs. One pivotal aspect of the trial conduct is maximizing clinician engagement. Methods/Results: Clinician engagement can be diminished by barriers including time limitations, insufficient research infrastructure, lack of research training, inadequate compensation for research activities, and clinician beliefs. We used several key approaches to boost clinician engagement such as empowering clinician champions, including a variety of clinicians, nurses and advanced practice providers, periodic newsletters and coordinated team celebrations, and deploying novel technological solutions. Specifically, some centers generated electronic health records–based best practice advisories and research dashboards. Future large pragmatic trials will benefit from standardization of the various clinician engagement strategies especially studies leveraging electronic health records–based approaches like research dashboards. Financial or academic "credit" for clinician engagement in clinical research may boost participation rates in clinical studies. Conclusion: Maximizing clinician engagement is important for the success of clinical trials; the strategies employed in the ADAPTABLE trial may serve as a template for future pragmatic studies.